The Impact of ESG Reporting to Corporate Value: A Literature Review - I Gusti Agung Krisna Pramadhi (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
In conducting its business, a company always strives to increase profits and maximise investor wealth, which in turn impacts the company's value. One of the keys to this is the implementation of Environment, Social, and Governance (ESG), which covers aspects of environmental sustainability, social issues, and corporate governance. The implementation of ESG can be seen in the company's sustainability reports. ESG is a standard designed to evaluate and regulate environmental, social, and corporate performance in companies. This study aims to discuss the results of previous studies related to the influence of ESG on company value. The method used is a literature review. The study shows that research has produced inconsistent results regarding the impact of ESG on company value, with a tendency for ESG reporting to have no significant effect and a tendency for ESG performance to have a positive effect. It is also mentioned that awareness of the importance of ESG in companies is still relatively low, so that companies and investors do not pay much attention to the implementation of ESG in companies.